A cellular model reflecting the phenotypic heterogeneity of mutant HRAS driven squamous cell carcinoma. Issue 5 (5th May 2016) - Cantariño, Neus; Fernández‐Figueras, M. Teresa; Valero, Vanesa; Musulén, Eva; Malinverni, Roberto; Granada, Isabel; Goldie, Stephen J.; Martín‐Caballero, Juan; Douet, Julien; Forcales, Sonia‐Vanina; Buschbeck, Marcus
Abstract : Squamous cell carcinomas have a range of histopathological manifestations. The parameters that determine this clinically observed heterogeneity are not fully understood. Here, we report the generation of a cell culture model that reflects part of this heterogeneity. We have used the catalytic subunit of human telomerase hTERT and large T to immortalize primary UV‐unexposed keratinocytes. Then, mutant HRAS G12V has been introduced to transform these immortal keratinocytes. When injected into immunosuppressed mice, transformed cells grew as xenografts with distinct histopathological characteristics. We observed three major tissue architectures: solid, sarcomatoid and cystic growth types, which were primarily composed of pleomorphic and basaloid cells but in some cases displayed focal apocrine differentiation. We demonstrate that the cells generated represent different stages of skin cancerogenesis and as such can be used to identify novel tumor‐promoting alterations such as the overexpression of the PADI2 oncogene in solid‐type SCC. Importantly, the cultured cells maintain the characteristics from the xenograft they were derived from while being amenable to manipulation and analysis. The availability of cell lines representing different clinical manifestations opens a new tool to study the stochastic and deterministic factors that cause case‐to‐case heterogeneity despite departing from the same set of oncogenes and the same genetic background. Abstract : What's New? The histopathological heterogeneity encountered in non‐melanoma skin tumours and even within the same tumour class such as squamous cell carcinoma (SCC) is still poorly understood. Here, the authors report the generation of a set of cell lines that reflect part of SCC heterogeneity and represent different stages of skin cancerogenesis. The model has the potential to be used as a unique tool for the study of genetic and non‐genetic mechanisms underlying case‐to‐case heterogeneity. It also offers a linear model for the discovery of novel cancer driver genes and the development of drugs targeting Ras proteins or their downstream signaling components.